Optimization of cutting parameters of microwave expanded stem in slim cigarette. Issue 3 (January 2021) - Pan, Wen; Feng, Hongtao; Chen, Ran; Li, Xin; Hu, Qun; Yang, Lei; Wu, Jiacan; Zou, Juan; He, Xufeng; Pu, Qian; Zhao, Meiwei; Qiu, Ye; et al.
Abstract: In order to explore the cutting optimization parameters of the processing technology of the expanded stem of slim cigarette, according to the quality characteristics of the microwave expanded stem, the samples with different combinations of cutting parameters were optimized. The results showed that under the combination of cutting parameters with a slicing thickness of 0.5mm and cutting width of 0.2mm, the high whole cut tobacco ratio, moderate small particle content, and minimum tobacco loss from cigarette end could be obtained. At the same time, the samples also had a lower hazard index and better sensory quality. This study provides a reference for technical research on the processing technology of the expanded stem of slim cigarettes.